An intraosseous malignant peripheral nerve sheath tumor in the mandible of a patient with neurofibromatosis type 1. Issue 2 (11th June 2018) - Takaichi, Mayu; Tomihara, Kei; Fujiwara, Kumiko; Imaue, Shuichi; Miwa, Shigeharu; Noguchi, Makoto
Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are sarcomas that originate in peripheral nerves or neurilemma cells. Here, we report an extremely rare case of an intraosseous MPNST in the mandible of a patient with neurofibromatosis type 1 (NF1). A 57‐year‐old woman with a history of NF1 was referred to our hospital because she had abnormal sensations at her left mandible. She was diagnosed with MPNST and underwent radical resection, although local recurrence and multiple metastases were detected during follow‐up. Despite receiving palliative radiotherapy, the patient died at 13 months after the initial diagnosis.